Pengaruh Pengetahuan Akuntansi, Pengalaman Usaha Dan Skala Usaha Terhadap Penggunaan Informasi Akuntansi Pada Pelaku UMKM - Siti Dian Astuti; Rohma Septiawati; Ade Trisyanto (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to obtain evidence on the impact of accounting knowledge, business experience, and business scale on the utilization of accounting information among SME (Small and Medium-sized Enterprises) operators in the East Telukjambe District. The research focus is on micro-scale enterprises in the East Telukjambe area, Karawang Regency. Employing the Slovin formula, 77 participants were selected as the sample. Data collection was conducted through questionnaire distribution to respondents. The research findings indicate that accounting literacy and business tenure significantly influence the use of accounting information, whereas business size does not demonstrate a significant effect on the application of such accounting data.